Penerapan Model Pembelajaran Kooperatif Picture and Picture dalam Meningkatkan Hasil Belajar Mata Pelajaran Biologi Materi Pokok Pembelahan Sel Kelas XII-MIA 2 di SMAN 5 Kota Jambi Tahun Ajaran 2018/2019 - Reflina Reflina (Universitas Batanghari Jambi, 2020)
This study aims to determine the application of picture and picture cooperative learning methods in improving student learning outcomes in class XII-MIA SMAN 5 Kota Jambi. This research is a Classroom Action Research (CAR) on students of class XII-MIA SMAN 5 Kota Jambi. In this study, researchers used a class to implement the picture and picture model, namely class XII-MIA2 SMAN 5 Kota Jambi, which consisted of 40 students, consisting of two cycles, each cycle including the steps of planning, implementing actions, observing and reflecting. In the planning stage, a learning scenario is prepared and a learning tool is prepared. In implementing the action, the learning process is carried out with a picture and picture model. Observation results are presented in class discussions. Observation results are presented in class discussions, while observations are made of student activities, student attitudes, and teacher performance as well as learning outcomes tests. Performance indicators in research in the form of achievement of mastery learning individually and classically. The results of the implementation of the first cycle showed that the performance indicators had not been achieved, for this reason there were improvements to the second cycle. Analysis in cycle II shows the completeness of student learning outcomes.